Time‐Dependent Morphology Evolution of Solution‐Processed Small Molecule Solar Cells during Solvent Vapor Annealing. Issue 10 (1st March 2016) - Min, Jie; Jiao, Xuechen; Ata, Ibrahim; Osvet, Andres; Ameri, Tayebeh; Bäuerle, Peter; Ade, Harald; Brabec, Christoph J.
Abstract : Morphological modification using solvent vapor annealing (SVA) provides a simple and widely used fabrication option for improving the power conversion efficiencies of solution‐processed bulk heterojunction (BHJ) small molecule solar cells. Previous reports on SVA have shown that this strategy influences the degree of donor/acceptor phase separation and also improves molecular donor ordering. A blend composed of a dithienopyrrole containing oligothiophene as donor (named UU07) and [6, 6]‐phenyl‐C61‐butyric acid methyl ester as acceptor is investigated with respect to SVA treatment to explore the dynamics of the BHJ evolution as a function of annealing time. A systematic study of the time dependence of morphology evolution clarifies the fundamental mechanisms behind SVA and builds the structure–property relation to the related device performance. The following two‐stage mechanism is identified: Initially, as SVA time increases, donor crystallinity is improved, along with enhanced domain purity resulting in improved charge transport properties and reduced recombination losses. However, further extending SVA time results in domains that are too large and a few large donor crystallites, depleting donor component in the mixed domain. Moreover, the larger domain microstructure suffers from enhanced recombination and overall lower bulk mobility. This not only reveals the importance of precisely controlling SVA time on gaining morphological control, but also provides a path toward rational optimization of device performance. Abstract : Time‐dependent morphology evolution of solution‐processed small molecule solar cells during solvent vapor annealing is systematically and methodically investigated. This not only reveals the importance of precisely controlling SVA time on gaining morphological control, but also provides a path toward the rational optimization of device performance.